Queering Aby Warburg: visual culture and “emotional resistances” in Torremolinos during the sixties and the seventies. - Cuevas-del-Barrio, Javier (My University, 2018)
This paper proposes an epistemological approximation between the method of visual analysis developed by Aby Warburg in Atlas Mnemosyne, and the concept of "emotional resistances" proposed by Eve Kosofsky Sedgwick with the intention of developing "reparative epistemologies" (Touching Feeling. Affect, Pedagogy, Performativity, Duke, 2003). The construction of a queer cartography from Warburg's Atlas Mnemosyne is a project of great magnitude. This is the reason why we want to start from a g-local conception (global and local), and apply this methodology to the analysis of the traces and practices of personal photography that were developed in the Sixties and Seventies in the LGTBQ+ community of Torremolinos (Spain), as an example of cultural practice that allows to recover the "emotional resistances", especially of the members of this community with which the Francoist “emotional regime” (1939-1975) fattened. We will use a queer counter-methodology: the protagonists of the 1970s preserve experiences, memories and materials in the form of personal collections, which sometimes find themselves in a precarious drift that makes militant archival work indispensable. These photographs show the role that Torremolinos had in the Sixties and Seventies as a destination for the LGTBQ+ community in Europe and the development of activism in Spain. This is the reason why in January 1977 the Democratic Union of Homosexuals (UDH) was created in Málaga, months before the first demonstration for the repeal of the Ley de Peligrosidad y Rehabilitación Social (LPRS) in Barcelona in June 1977. The analysis of these photographs will be carried out taking into account both Aby Warburg's method (mainly the Pathosformel and the assembly concept present in the Atlas Mnemosyne) and Eve Kosofsky's concept of "emotional resistences".
Keywords: Aby Warburg - Crítica e interpretación; Homosexualidad; Art History; Queer theory; Eve Kosofsky Sedgwick; Torremolinos